Crystallising galactocele of the breast: a rare cytological diagnosis. Issue 5 (25th May 2021) - Varshney, Bharti; Bharti, Jyotsna Naresh; Saha, Souvik; Sharma, Naveen
Abstract : Galactocele of the breast is a benign condition characterised by milk containing cystic lesions, usually present during pregnancy and lactation. The diagnosis of galactocele is difficult due to physiological changes which occur during pregnancy and lactation. Fine needle aspiration cytology proves to be a simple and minimally invasive procedure in diagnosing and treating this condition. Very rarely, long-standing galactoceles can show crystal formation on aspirate smears, termed as crystallising galactocele. Herein, we present this rare case of crystallising galactocele in a 26-year-old lactating woman. We are reporting this case because of its rarity, as less than 10 cases have been reported so far.